National identity and economic activity of Ukrainian population: Relationship and differences in the regions - Ievhen Ovcharenko; Inna Semenenko (Contemporary Economics, 2022)
This research examines the relation between the levels of national identity of Ukrainians in different regions of the country and the current state of their economic activity. The study explores whether the changes in economic activity of Ukrainian population are related to the changes in the level of its national identity. We used the results of the national poll, conducted by the sociological agency in Ukraine, together with data from State Statistics Service in Ukraine. The indicators of linguistic, civic and cultural identity were compared to regional human development indices, and indicators of socio-demographic status and economic activity of population in five aggregative regions in Ukraine. The results showed how differently people within the same country perceive social and economic standards of living and have various perceptions of the basis of their own national identity. This affects the processes of national identification and establishment of emphasis in regional development paths, as well as contributes to definition of the most relevant to a particular region levers of economic influence on the processes of national identification.
Keywords: A13; Z13; R10; O52; 330; National identity; identification; economic activity; human development